The main differences between connective tissue diseases-associated interstitial lung disease and idiopathic pulmonary fibrosis - Karataş, Ahmet; Öz, Burak; Pişkin Sağır, Rabia; Gür, Mustafa; Koca, Süleyman Serdar (Galenos Publishing House, 2021)
Connective tissue diseases (CTD) can often cause respiratory system involvement. Interstitial lung disease (ILD) is an example of respiratory system involvement, which is the most frequent cause of mortality and morbidity, which challenges patients and their physicians in routine practice. Idiopathic pulmonary fibrosis (IPF) is another common cause of ILD. Similarities between CTD-ILD and IPF in terms of pathogenic, clinical and radiological findings complicate the distinction of the two diseases. However, the treatment of CTD-ILD and IPF is very different. Therefore, it is very important to distinguish both. ILD is grouped histopathologically and radiologically as usual interstitial pneumonia (UIP), non-specific interstitial pneumonia (NSIP), lymphocytic interstitial pneumonia (LIP) and organized pneumonia. Patients with CTD-ILD in the NSIP pattern have a better response to immunosuppressive therapy than patients with the UIP pattern. The effectiveness of antifibrotic therapy is more prominent in patients with the UIP pattern. While IPF is in the UIP pattern, CTD-ILD is often in the NSIP pattern. However, rheumatoid arthritis may be in the UIP pattern and Sjögren’s syndrome in the LIP pattern. © 2021 by the Turkish Society for Rheumatology/Journal of Turkish Society for Rheumatology published by Galenos Publishing House.
Bağ dokusu hastalıkları ile ilişkili interstisyel akciğer hastalığı ile idiyopatik pulmoner fibroz arasındaki temel farklar
Keywords: Connective tissue diseases; idiopathic pulmonary fibrosis; interstitial lung disease